Comparison of Frozen Green Jackfruit Quality following Boiling Water and Microwave Blanching - Taslima Ayesha Aktar Nasrin; Md. Atiqur Rahman; Most. Sadia Arfin; Mohammad Mainuddin Molla; Ashfak Ahmed Sabuz; Most Tahera Naznin; Md. Abdul Matin (Food ScienTech Journal, 2024)
Although jackfruit is highly nutritious, it has a high postharvest loss and is only available for a limited time, especially the green type. Therefore, preservation is required to ensure its availability throughout the year. Green Jackfruit can be preserved by freezing; however, blanching is necessary to retain its nutrients and colour before freezing. So, the aim of this study is to examine the effects of boiling water and microwave blanching on the quality of green jackfruit both during freezing and just after blanching. Jackfruits were cleaned, peeled, and cut into one cm thick slices after removing core. Slices were blanched in boiling water (100°C) and microwave (input power 1500 W) and stored for 8 months in a freezer (-20°C) after chilling. Blanching was faster in microwave (2.5 min) than in boiling water (3 min).  At eight months, unblanched jackfruit slices received 3.87 scores (considered unacceptable), but slices blanched in boiling water and microwave obtained 6.45 and 6.88 scores respectively in case of overall acceptability, which are considerably higher (p < 0.05) than their unblanched counterparts.